Friendship across the seas the US Navy and the Japan Maritime Self-Defense Force = Umi no yūjō - Agawa, Naoyuki (Tokyo, Japan Japan Publishing Industry Foundation for Culture, 2019)
"This book describes the history of the relationship between the Japan Maritime Self-Defense Force (JMSDF), the heir to the Imperial Japanese Navy (IJN), and the United States Navy (US Navy). The two navies fought each other fiercely on the seas and in the air during the Pacific War. Each found the other a formidable enemy. They came to respect each other in action. Soon after the war, when the Cold War turned hot, they began to work together as allies. With the generous assistance of the US Navy, the JMSDF was established as its counterpart. Doing so was in their respective national interests, but many individual officers and sailors on both sides had mixed feelings about working with their former enemies. Over the years, however, these two navies have gradually built strong ties, with respect for and trust in each other. This was made possible by conducting countless joint operations at sea. Leaders of the US Navy began to realize that this small maritime force, its actions being restrained in so many ways by domestic politics as well as constitutional and legal limitations, does its job well, is reliable, and can be fully trusted. The JMSDF realized that, in the Asia/Pacific region, there was no other navy with which it shares common interests and values to be allied with. Close to seventy years of accumulated shared experiences have transformed an initially timid and unbalanced relationship into one of, if not the, most successful navy-to-navy partnership in the world. The maritime alliance between Japan and the United States today is anchored in this history. Numerous admirals, officers, and sailors of the two navies working together have greatly contributed to the stability and prosperity of the Asia/Pacific region for the past seventy years. They are not Nimitzes or Yamamotos, but are nevertheless heroes who toiled hard to bring about this unique friendship across the seas."
James E. Auer and the Japan Maritime Self-Defense Force -- Kazutomi Uchida, the JMSDF Chief of Staff -- Teiji Nakamura, the JMSDF Chief of Staff -- Minesweepers crossing the sea -- Arleigh Burke and the foundation of the JMSDF -- Mr. Navy: Ichirō Masuoka -- The US Navy's war generation -- A dogwood in Etajima, a cherry tree in Annapolis -- Minesweepers crossing the sea again -- Friendship across the seas after the Gulf War -- Friendship across the seas today.
Originally published in Japanese under title Umi no yūjō: Beikoku Kaigun to Kaijō Jieitai by Chūō Kōron Shinsha, in 2001.
Includes bibliographical references (pages 305-306).
Keywords: United Stated Navy--Officers.